A bone-targeting drug delivery vehicle of a metal–organic framework conjugate with zoledronate combined with photothermal therapy for tumor inhibition in cancer bone metastasis. (7th March 2022) - Ge, Ting; Weiwei, Zhang; Ge, Fei; Zhu, Longbao; Song, Ping; Li, Wanzheng; Gui, Lin; Dong, Wan; Tao, Yugui; Yang, Kai
Abstract : Synthesis of 5-Fu/ICG@ZIF-90-PEG-ZOL. Design based on bone-targeted modification on the surface of nanocarrier with ZOL, and also in combination chemotherapy and photothermal therapy (created in BioRender.com). Abstract : Chemotherapy is a conventional treatment method for metastatic bone cancer, but it has limitations, such as lower drug-targeting of bone tissues and serious side effects. Bone metastasis almost always occurs in advanced cancer, and most patients in this period have strong drug resistance, which further worsens the curative effect. To address the above-mentioned difficulties, a drug delivery platform is proposed in this paper that accomplishes the bone-targeting of drugs to efficiently inhibit tumors. First, the anti-cancer drugs 5-fluorouracil (5-Fu) and indocyanine green (ICG) were loaded into a zeolitic imidazolate framework (ZIF-90) to form 5-Fu/ICG@ZIF-90. Polyethylene glycol with zoledronic acid (ZOL) was encapsulated using 5-Fu/ICG@ZIF-90 to synthesize 5-Fu/ICG@ZIF-90-PEG-ZOL nanoparticles, which showed dimensional stability, good thermal stability, and bone-targeting ability. Second, the in vitro anti-cancer activity of the designed platform was investigated using cytotoxicity, apoptosis, live–dead staining, cell cycle, and cell ultrathin section analysis. The results indicated that the nanoparticles inhibited MCF-7 cell activity when chemotherapy was combined with PTT. Finally, H&E staining and TUNEL detection were performed in mouse organs and tumors. The nanoparticles combined with photothermal therapy (PTT) and triggered by near-infrared irradiation induce apoptosis of tumor cells in vivo, displaying a better efficacy of combined chemotherapy and photothermal therapy. Experiments conducted on the 5-Fu/ICG@ZIF-90-PEG-ZOL nanoparticles demonstrated their promising performance for cancer bone metastasis inhibition.